Multiple analytic solutions for irreversible mechanism and Joule heating impact on dissipative micropolar fluid flow driven by stretching/shrinking surface with PST and PHF boundary conditions - Sachhin, S. M.; Bharath, M. S.; Sachin, G. M.; Mahabaleshwar, U. S.; Laroze, D.; Öztop, Hakan Fehmi (Elsevier, 2025)
The current research aims to examine the Joule heating and magnetic field influence on micro-polar fluid flow across expanding surface, which is is significant in enhancing the efficiency in biomedical and engineering fields, In this analysis, examined the influence of entropy generation, magnetic field, porous medium, and prescribed boundary restrictions. To the best of authors knowledge, no prior research has studied all these effects simultaneously, which emphasizes the originality of the current analysis. The considered governing partial differential equations are transformed to ordinary differential equations by using similarity expressions and then formulated analytically using hypergeometric series solutions. The dual solutions have been extracted from the current analysis which offers deeper insights into the micropolar fluid behaviour under considered physical effects. The outcomes of the present analysis reveal that enhancing the porous media and magnetic field reduces the momentum by 15 %. With enhancing the internal heat source enhances the temperature by 20 %, and thermal radiation enhances temperature by 29 %, enhancing the viscosity ration reduces the velocity by 23 %. These results help in analysing the blood movement modelling, advanced medical therapies, and magnetic drug delivery among others.
Keywords: Analytical framework; Entropy analysis; Ohmic heating; Micropolar fluid; Multiple solutions